مصطلح "التردد" عند الشيخ خليل من خلال كتاب مواهب الجليل - موسى طبراخ; بدر الدين هشام خموري; د/نعيمي زيغمي (جامعة عمار ثليجي الاغواط, 2023)
he title of the note: The term "hesitation" according to Sheikh Khalil through the book of talents of the Galilee - the chapter on financial transactions that are forbidden as a model -. The note consists of an introduction, two chapters, a conclusion, and an index. Introduction: It includes the importance of the topic, the reasons for choosing the topic, the research objectives, the approach followed, the methodology of the research, previous studies, the difficulties of the research, the preparatory form of the study, and the research plan. The first chapter: we dealt with a translation of Sheikh Khalil, introducing his abbreviation, then we moved on to translating Sheikh Al-Hattab, and introducing his book, Talents of Galilee. The second chapter: we examined the concept of the descending dispute linguistically and idiomatically, then the concept of the descending disputعنوان المذكرة: مصطلح التردد عند الشيخ خليل من خلال كتاب مواهب الجليل- باب المعاملات المالية المنهي عنها نموذجا.- تتكون المذكرة من مقدمة، وفصلين، وخاتمة، وفهرس. المقدمة: وتشمل على أهمية الموضوع، وأسباب اختيار الموضوع، وأهداف البحث، والمنهج المتبع، ومنهجية البحث، والدراسات السابقة، وصعوبات البحث، والإشكال الممهد للدراسة، وخطة البحث. الفصل الأول: تناولنا فيه ترجمة للشيخ خليل، والتعريف بمختصره، ثم انتقلنا إلى ترجمة الشيخ الحطاب، والتعريف بكتابه مواهب الجليل. الفصل الثاني: وقفنا فيه على مفهوم الخلاف النازل لغة واصطلاحا، ثم مفهوم الخلاف النازل التردد عند الشيخ خليل، وكذلك مفهوم المعاملات المالية لغة واصطلاحا. وتضمن كذلك الفصل الثاني الجانب التطبيقي، تمثل في مسائل التردد في باب البيوع، ومسائل التردد في باب الربا. الخاتمة: تعرضنا فيها لأهم النتائج المستخلصة من البحث، ثم أهم التوصيات، وأما الفهرسe "hesitation" according to Sheikh Khalil, as well as the concept of financial transactions linguistically and idiomatically. The second chapter also included the practical side, represented in the issues of hesitation in the section on sales, and the issues of hesitation in the section on usury. Conclusion: We presented the most important results drawn from the research, then the most important recommendations. As for the index, it includes the research topics.